1979
DOI: 10.1094/phyto-69-1176
|View full text |Cite
|
Sign up to set email alerts
|

Verticillium Wilt on Resistant Tomato Cultivars in California: Virulence of Isolates from Plants and Soil and Relationship of Inoculum Density to Disease Incidence

Abstract: Verticillium wilt caused by race 2 of Verticillium dahliae is common in proportions) was about 5.7 ms per gram of, soil. In five other fields, California on tomato cultivars with the Ve gene for resistance to race 1. however, in which the numbers of race 2 ms were determined, a linear About 47% of 124 isolates of V. dahliae taken directly from tomato field correlation was observed between numbers of race 2 ms (0.0 to 2.0 ms/g of 'soils were race 2; the remaining isolates were either race 1 (43%) or soil) and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
64
1
8

Year Published

1989
1989
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 0 publications
6
64
1
8
Order By: Relevance
“…Similar variation previously has been observed for isolates of V. dahliae pathogenic on tomato, potato, and cotton (3,10,14,24). Grogan et al (10) found that isolates of V. dahliae obtained from commercial tomato fields varied in virulence for both races, with race 1 isolates typically exhibiting greater virulence compared with race 2 on a tomato cultivar lacking the Ve genes. Although it appears that similar variation for virulence exists among race 2 isolates on lettuce based on three tested isolates, the race 2 isolate VdLs17 was as virulent on susceptible lettuce cultivars as several race 1 isolates.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Similar variation previously has been observed for isolates of V. dahliae pathogenic on tomato, potato, and cotton (3,10,14,24). Grogan et al (10) found that isolates of V. dahliae obtained from commercial tomato fields varied in virulence for both races, with race 1 isolates typically exhibiting greater virulence compared with race 2 on a tomato cultivar lacking the Ve genes. Although it appears that similar variation for virulence exists among race 2 isolates on lettuce based on three tested isolates, the race 2 isolate VdLs17 was as virulent on susceptible lettuce cultivars as several race 1 isolates.…”
Section: Discussionsupporting
confidence: 73%
“…It was speculated that their appearance was due to the spread of a new recombinant or mutant isolate or to the selection of endemic race 2 isolates, because of the widespread use of the Ve resistance genes in tomato production (10,17,24). Regardless of the race, a continuum of virulence exists among isolates of V. dahliae pathogenic on tomato, suggesting that considerable genetic variation at loci other than those critical to the specificity of Ve genes also exists (10,17,24). Similar findings regarding the existence of a continuum of virulence among isolates of V. dahliae also were made in crops like cotton (3) and potato (14).…”
Section: This Article Is From the December 2006 Issue Of Published Bymentioning
confidence: 99%
“…It is possible that race 1 isolates may be more fit than race 2 isolates and, thus, would become more prevalent in the field with subsequent lettuce crops (strawberry was the crop grown immediately prior to the 2004 experiment). Grogan et al (8) found differences in virulence between race 1 and race 2 tomato isolates of V. dahliae on susceptible cultivars, with race 1 being the more virulent. However, such differences in virulence were not apparent between the race 1 and race 2 lettuce isolates used in the experiments described here (24).…”
Section: Discussionmentioning
confidence: 99%
“…MS in soil are the primary source of inoculum for V. dahliae infections in host plants (21). Incidence of Verticillium wilt in herbaceous hosts is generally proportional to the number of MS in soil (11,12,19), but can vary considerably depending on the cultivar and crop (5,6,8,21). For example, in cauliflower, 4 MS g -1 of dry soil can cause 16% wilt incidence but 10 MS g -1 of soil causes 50% wilt (21).…”
mentioning
confidence: 99%
“…For example, in cauliflower, 4 MS g -1 of dry soil can cause 16% wilt incidence but 10 MS g -1 of soil causes 50% wilt (21). In tomato, 0.5 MS g -1 of soil causes 50% wilt incidence but 6 MS g -1 of soil causes 100% wilt (5). In strawberry, however, as little as 0.3 MS g -1 of soil causes 5% wilt and just 2 MS g -1 of soil can cause 100% wilt (6).…”
mentioning
confidence: 99%